Accuracy Analysis of Latin-to-Balinese Script Transliteration Method - I N. Jampel; Gede Indrawan; I W. Widiana (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Balinese script writing, as one of Balinese cultural richness, is going to extinct because of its decreasing use. This research is one of the ways to preserve Balinese script writing using technological approach. This research focused on accuracy analysis of Latin-to-Balinese script transliteration method on mobile application since mobile computing becomes more important way on preservation effort. This analysis used an existing method from few research in this area, i.e. method on mobile application that was called Transliterasi Aksara Bali (TAB). The analysis was based on certain document of Balinese script writing rules and examples. Through the experiment, TAB was considered has accuracy over 68% (103 of 151) cases and improvement recommendation on thirteen kind of special words. This research contributes on the accuracy analysis and that recommendation for future development of Latin-to-Balinese script transliteration method.